2001
DOI: 10.1002/1097-4636(200107)56:1<144::aid-jbm1079>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the effect of virtual crosslinking on the hydrolytic stability of novel aliphatic polyurethane ureas for blood contact applications

Abstract: The effect of virtual crosslinking on the hydrolytic stability of completely aliphatic novel poly(urethane ureas), HFL9-PU1 (hard-segment content 57.5%) and HFL13-PU2 (hard-segment content 67.9%) based on 4,4'-methylene bis(cyclohexyl isocyanate) (H(12)MDI)-hydroxy-terminated polybutadiene-1,6-hexamethylene diamine, was studied. Fourier transform infrared-attenuated total reflectance and wide-angle X-ray diffraction studies revealed hydrogen-bonding interaction and microphase separation and formation of crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 39 publications
3
28
0
Order By: Relevance
“…A novel proprietary segmented polyurethane urea, HFL18‐PU, was synthesized using a cycloaliphatic diisocyanate, 4,4′‐methylene bis(cyclohexyl isocyanate) (H 12 MDI), an aliphatic unsaturated hydrocarbon polyol hydroxyl terminated polybutadiene (HTPBD), and hexamethylene diamine (HDA), toluene‐dimethyl acetamide solvent and dibutyl tin laurate catalayst as reported earlier 9–11. Initially the prepolymer was prepared using HTPBD and H 12 MDI, and the prepolymer was chain extended with HDA.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A novel proprietary segmented polyurethane urea, HFL18‐PU, was synthesized using a cycloaliphatic diisocyanate, 4,4′‐methylene bis(cyclohexyl isocyanate) (H 12 MDI), an aliphatic unsaturated hydrocarbon polyol hydroxyl terminated polybutadiene (HTPBD), and hexamethylene diamine (HDA), toluene‐dimethyl acetamide solvent and dibutyl tin laurate catalayst as reported earlier 9–11. Initially the prepolymer was prepared using HTPBD and H 12 MDI, and the prepolymer was chain extended with HDA.…”
Section: Methodsmentioning
confidence: 99%
“…The in vitro calcification of candidate polyurethane urea was evaluated using metastable calcium phosphate solution as reported elsewhere 14, 15. Polyurethane urea strips of rectangular shape (0.5 × 5 cm 2 ) were stressed equally by bending the specimens and immersed in calcium phosphate metastable solution in screw capped test tubes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…b (Content of solubilized carbon)/(content of carbon in polymer) Â 100, (D/T in Table 3). reported that completely aliphatic poly(urethane urea) based on 4,4 0 -methylene biscyclohexyl isocyanate/hydroxyterminated polybutadiene/1,6-hexamethylene diamine did not degrade by papain after 30 days at 37°C [13]. These facts can be explained by the surface hydrophobic properties of the polymers.…”
Section: Spuus Degradation Of Spuus By Various Proteasesmentioning
confidence: 99%
“…The enzymatic degradation of segmented polyurethanes and polyurethane ureas has been studied by several groups of researchers in the field of biomedical materials. The enzymes mainly used are chymotrypsin [6][7][8][9], papain [10][11][12][13][14], and cholesterol esterase [15][16][17], to ensure the cleavage of urethane bonds and the structure of the degradation products. Meanwhile, lysine diisocyanate (LDI) based polyurethanes, which are considered to give non-toxic degradation products, are suitable biomaterials for tissue engineering, such as scaffold materials [3,6,9,[18][19][20].…”
Section: Introductionmentioning
confidence: 97%